The Response and Pattern of Community Management for the Variety of Poverty Alleviation Assistance in the Fishermen's Village, across Belawan - Bakhrul Khair Amal (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2018)
The method of social phenomenology is seen as appropriate to describe the dimensions of poverty so that reality will be found in the "Poor Village" of the Village of Fishermen across the country. The intersection between Marxist thinking, Chambers and the phenomenological method lies in the unit of analysis. The unit of analysis in the phenomenology method lies in the subjectivity that leads to things that appear around, so that the facts presented are facts in accordance with what is felt by the subject under study. If it is associated with Marxist perspectives that talk a lot about class, which in other words there are actors or actors in the class. The state provides assistance to poor families as a solution to poverty alleviation, but in reality the assistance provided by the State preserves poverty.